2002
DOI: 10.1074/jbc.m204707200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling Identifies Two Members of the ATP-binding Cassette Transporter Superfamily Required for Sterol Uptake in Yeast

Abstract: In contrast to lipoprotein-mediated sterol uptake, free sterol influx by eukaryotic cells is poorly understood. To identify components of non-lipoprotein-mediated sterol uptake, we utilized strains of Saccharomyces cerevisiae that accumulate exogenous sterol due to a neomorphic mutation in the transcription factor, UPC2. Two congenic upc2-1 strains, differing quantitatively in aerobic sterol uptake due to a modifying mutation in the HAP1 transcription factor, were compared using DNA microarrays. We identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
297
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(308 citation statements)
references
References 36 publications
6
297
2
1
Order By: Relevance
“…Previous experiments have shown that ABC transporters are able to translocate membrane phospholipids and sterols and function in controlling or modulating membrane lipid homeostasis, regulation of membrane permeability and phospholipid bilayer distribution (Wilcox et al, 2002;Li and Prinz, 2004). In Saccharomyces cerevisiae cells producing high levels of carotenoids, the membrane buffering capacity to accumulate the produced carotenoids may not be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that ABC transporters are able to translocate membrane phospholipids and sterols and function in controlling or modulating membrane lipid homeostasis, regulation of membrane permeability and phospholipid bilayer distribution (Wilcox et al, 2002;Li and Prinz, 2004). In Saccharomyces cerevisiae cells producing high levels of carotenoids, the membrane buffering capacity to accumulate the produced carotenoids may not be sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, two additional plasma membrane PDRtransporters, Aus1p and Pdr11p, may be involved in sterol uptake when endogenous sterol biosynthesis is impaired, as for example during anaerobic growth [19]. AUS1 is also upregulated in response to azole treatment [20], implying that it could mediate drug efflux.…”
Section: Plasma Membrane Abc Transporters -The First Defense Linementioning
confidence: 99%
“…Based on genome-wide transcriptional profiling of a Upc2-1 gain-of-function mutant strain that exhibits aerobic sterol influx, PDR11 and AUS1 were identified as major determinants required for uptake of free sterols under conditions of impaired ergosterol biosynthesis [19].…”
Section: Regulation Of Abc Gene Expression In S Cerevisiaementioning
confidence: 99%
“…These proteins then mediate sterol influx. Presumably, other proteins contribute to this process as well (Wilcox et al, 2002;Alimardani et al, 2004).Here, we characterize the link between proteins regulating sterol uptake and the PAKs Ste20, Cla4 and Skm1. Our data suggest a model (Figure 1), according to which PAKs shuttle into the nucleus, where they interact with Sut1 and possibly other transcriptional regulators and down-regulate the expression of AUS1, DAN1, and PDR11.…”
mentioning
confidence: 99%
“…Sterol uptake is controlled by the transcriptional regulators Sut1, Upc2, and Ecm22, which are members of the Zn(II)2Cys6 family of DNA-binding proteins (Schjerling and Holmberg, 1996). Under anaerobic conditions, Upc2 and Sut1 up-regulate the expression of the ATP-binding cassette transporter AUS1 and PDR11, and the putative cell wall mannoprotein DAN1 (Figure 1) Wilcox et al, 2002;Alimardani et al, 2004). These proteins then mediate sterol influx.…”
mentioning
confidence: 99%